SYSTEMATIC LITERATURE REVIEW: THE EFFECT OF TOTAL REWARD SYSTEM ON EMPLOYEE JOB SATISFACTION AND PERFORMANCE - Kevin Ghulaman Silmi; Sopiah; Arief Noviarakhman Zagladi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study systematically reviews 64 articles exploring the impact of total reward systems on job satisfaction and employee performance. Utilizing a Systematic Literature Review (SLR) approach based on the PRISMA methodology, the research examines the effectiveness of both financial and non-financial compensation in enhancing productivity and motivation. Articles were sourced from prominent scientific databases using keywords such as "total reward," "job satisfaction," and "employee performance." Findings indicate a positive correlation between total rewards and job satisfaction, although effectiveness varies by industry and reward type. Identified research gaps include the long-term impact of non-financial rewards and the role of workplace culture in reward effectiveness. These findings provide valuable insights for academics and practitioners aiming to optimize reward systems.